Emberi jogok a Bibliában - Mészáros, István László (Díké - A Márkus Dezső Összehasonlító Jogtörténeti Kutatócsoport folyóirata, 2025)
This study shows that, although the terms ’human rights’ and ’fundamental rights’ are not found in the Bible, their essential content, the classical human freedoms and values they protect, are in fact an integral part of the Bible. Some of them, such as the protection and conservation of one’s own and those of one's neighbors liberty, body and life, marriage and family, property, good name and reputation of oneself and one's neighbour; the freedom to avoid false gods and false oaths and to observe the weekly Sabbath (a rest day), are protected in the Decalogue, which prohibits their violation. The universal obligations stated in the Decalogue point to universal rights that truly exist on the other side. Through conveying all these, the Bible played a decisive role regarding the fact that these freedoms and fundamental values were later concretely declared as natural or human rights and became part of the written law in the Judeo-Christian cultural sphere. As far as the legal antecedents themselves are concerned, it is vital to realise that the Decalogue is more than a set of religious and moral commandments in this respect as well. As part of the Mosaic Laws, it was the foundation of the legal system of the ancient state of Israel and therefore constitutes a legal historical fact that is still relevant today. It is therefore not an exaggeration to proclaim that the Decalogue can be considered the first universal declaration of human rights in the history of mankind, with a history stretching back several millennia.